Application of the GPSS / H language to a mining hauling problem - Ortiz Sánchez, Oswaldo (2012)
The GPSS/H (General Purpose Simulation system), is both a computer programming language and a discrete random simulation system. It is versatile, easy to write and can solve a wide range of problems many of them concerned with the mining industry. This language is non procedural designed for a special purpose which tries to anticipate what the programer is doing. Programs are of short computational code and similar to the problem being solved. The application example shows that for an 8 truck fleet hauling ore and waste from 4 hydraulically operated underground bins onto two unloading points at surface for ore and waste, it is required to add one additional bin to avoid queues and attain minimum operating cost.